Nutritional Status, Knowledge, and Dietary Practices among Women in Amaltari, Nawalpur (Madhyabindu Journal, 2026)
Malnutrition, which is a big problem in Nepal, and lack of quality of diet are the challenges that have created problems for women living in rural areas because they are the main people who prepare food, and all members of the family eat the food prepared by them, and the health of the family depends on them. In this regard, a descriptive cross-sectional study was conducted in Kawasoti 17 Amaltari, Nawalpur, with the aim of studying the nutritional knowledge, perception, and eating behaviour of rural women. Convenience sampling was used to recruit participants aged 15-79 years. A total of 120 women were interviewed with a structured interview schedule adopted from FAO guidelines and prior Nepali surveys. Participants were predominantly aged 30-39 years (37.5%), with most having secondary education (48.33 %) and normal BMI (70.83%). The primary data obtained from that study were analyzed using the SPSS version 16 program. According to the respondents, 90% of people in that community thought they would adopt non-vegetarian food for taste (43.33%), nutrition (21.66%), or as a source of strength (21.66%). To improve people's balanced food intake and reduce malnutrition, education should not only work but also be culturally sensitive, and if community-based awareness programs are conducted, similar food consumption habits and misconceptions in rural areas can be addressed.